Electronics - Bridgman, Roger Francis, 1940- (London ; New York : Dorling Kindersley, 1993)
Text and accompanying photographs trace the history, discoveries, and devices of the science of electronics.
Electricity and magnetism -- Electromagnetic waves -- Inductors and transformers -- Semiconductors -- Analog and digital -- Making microchips -- Microprocessors.
Includes index.
Wilson's Junior High School.
School Library Journal.
Horn Book.
8.6
5-8
Keywords: Electronics -- Juvenile literature; Electronics; Electronics; Electronics